After the End: The Death of a Child in Marie Darrieussecq's Tom est mort and Hèléne Cixous's Le Jour où je n' étais pas là. (9th December 2019) - Robson, Kathryn
The death of a child is typically seen as incommensurate, a limit-experience defying articulation and comprehension. In her most recent book, Literature in the Ashes of History (2013), the literary critic and trauma theorist Cathy Caruth theorizes a history that inscribes itself in and through its own (self-conscious, and traumatic) self-effacement; what is striking is that her attempt to theorize and initiate what she calls 'a new kind of language', produced 'After the End' (as she titles the second part of the book), must thus be understood not only in relation to the post-Holocaust world, but also in the context of the more personal, individual trauma of the loss of a child. This article seeks to explore Caruth's notion of a different kind of language through analysis of two French fictional representations of the death of a child published in this century: Marie Darrieussecq's novel Tom est mort, and Hèléne Cixous's autofictional novel, Le Jour où je n'étais pas là (2000). I read these texts (which both explicitly locate writing 'after the end') alongside Caruth's Literature in the Ashes of History to contemplate what it might mean to write 'after the end'. Tom est mort, I argue, experiments with linguistic form, self-consciously stammering — in a manner curiously similar to Caruth's — in its attempt to express the impact of the death of a child on the mother (and on her language). Cixous's text, by contrast, gives voice to the mother's impossible mourning through figures of absence and lack. The 'new language' announced by Caruth is in these texts not a new language in itself, rather a language that is articulated in and through its own erasure, disintegration and absence, that 'undoes' its subject even as it gives voice to it, and locates itself after an end that cannot be defined.